Signalling effects on symbolic status and travellers' well‐being in the luxury cruise industry - Loureiro, S. M. C.; Japutra, A.; Kwun, D. (International Journal of Tourism Research, 2019)
The purpose of this research is to examine the role of signalling effects of reputation and credibility on luxury cruise travellers' well-being and the mediating role of symbolic status (i.e., prestige and authentic pride). This study also explores the moderation effects of socio-economic status and past experiences. The results demonstrate noteworthy effects of reputation on prestige, authentic pride, and, subsequently, on travellers' well-being. The results also reveal the moderating role of socio-economic status between authentic pride and well-being. In addition, the results find significant differences between low- and high-experience groups in three relationships: reputation and prestige, credibility and prestige, and reputation and authentic pride.